Knowledge, Attitude and Practice of Women Regarding HIV/AIDS - Baral, Om Prasad (Academic Voices: A Multidisciplinary Journal, 2011)
HIV/AIDS is one of the most burning health problems in the world and Nepal is not an exception. It does not only affect individual's health but also socioeconomic condition. Its excessive prevalence is due to lack of literacy and awareness about it. It causes problems from womb to tomb. This study concludes that the majority of married women of child bearing age have inadequate knowledge and information about causes, mode of transmission, consequences and preventive measures of HIV/AIDS. Key words HIV/AIDS, behaviour of women, reproductive age, child bearing age DOI: http://dx.doi.org/10.3126/av.v1i0.5310 Academic Voices 2011; 1: 45-48